The Cranial Neural Crest in a Multiomics Era - Chong-Morrison, Vanessa; Sauka-Spengler, Tatjana (Frontiers in Physiology, 2021)
Neural crest ontogeny plays a prominent role in craniofacial development. In this Perspective article, we discuss recent advances to the understanding of mechanisms underlying the cranial neural crest gene regulatory network (cNC-GRN) stemming from omics-based studies. We briefly summarise how parallel considerations of transcriptome, interactome and epigenome data significantly elaborated the roles of key players derived from pre-omics era studies. Furthermore, the growing cohort of cNC multiomics data revealed contribution of the non-coding genomic landscape. As technological improvements are constantly being developed, we reflect on key questions we are poised to address by taking advantage of the unique perspective a multiomics approach has to offer.